Empirical Research and the Rate of Interest - Spiro, Alan (The Review of Economics and Statistics, 1958)
AS is well known, economic theory indicates that, in general, the interest rate will, ceteris paribus, have a greater effect upon longterm than upon short-term investment.' The purpose of this paper is to present a statistical test of this hypothesis. If this hypothesis is correct, we should expect that during periods when the interest rate fell that longer-term investment would tend to increase more rapidly (or decrease more slowly) than shorter-term investment, and conversely. On the average, investment by producers in construction represents a longer-term investment than investment in producers durables. In turn investment in producers durables is, on the average, of longer-term than investment in inventory. In addition, investment in residential construction is, on the average, of longer term than investment in consumers durables. The investment data for the economy as a whole can be conveniently contained within two fractions: